Full Employment and Social Justice Solidarity and Sustainability (Binzagr Institute for Sustainable Prosperity, 2018)
This edited collection investigates how full employment programs can sustain the economy and the environment, promote social justice, and reinvigorate local communities. The contributing authors focus on the formation of institutions to eliminate the opportunity gap for marginalized populations, enact environmentally sustainable methods of production and consumption, and rebuild local economies through education, training, and community redevelopment programs. They argue that the formation and implementation of a federally funded, locally operated Job Guarantee program is a vital component to address a variety of complex and interweaving concerns. Through the formation of alternative institutions and encouraging local economies, the Job Guarantee approach has the potential to alter economic, social, and political structures away from an exploitative market-oriented structure toward one that is refocused on humanity and the sustainability of the earth and its peoples, cultures, and communities. .